A systematic review of serious games as tools for STEM education - Tene, Talia; Vique López, Diego Fabián; Valverde Aguirre, Paulina Elizabeth; Cabezas Oviedo, Nilo Israel; Vacacela Gomez, Cristian; Bellucci, Stefano (Frontiers in Education, 2025)
ObjectiveSerious games are increasingly recognized as innovative tools in STEM (Science, Technology, Engineering, and Mathematics) education, providing engaging and interactive learning environments that can enhance student performance, engagement, and learning outcomes. This systematic review aims to synthesize current research on serious games in STEM education, evaluating their impact and identifying implications for educators, policymakers, and future research.MethodsA comprehensive literature search was conducted across Scopus, Web of Science, PubMed, and IEEE Xplore databases, yielding 584 articles. A total of 37 peer-reviewed journal articles met the inclusion criteria, guided by the PICOS framework, which focused on studies reporting the use of serious games in STEM education contexts. Data extraction included study characteristics, game types, participant demographics, educational contexts, and reported outcomes.AnalysisThe selected studies were analyzed to assess the effectiveness of serious games in enhancing learning outcomes, engagement, and performance in STEM education. The analysis also explored challenges related to the implementation of serious games, including technological limitations, the need for comprehensive educator training, and ethical considerations around data privacy, all of which may impact adoption in educational settings.ResultsSerious games demonstrated a positive impact on learning outcomes, such as knowledge acquisition, skill retention, and the application of STEM concepts, along with increased student engagement and motivation. These findings suggest that serious games can serve as valuable tools for educators seeking to foster active learning environments. For policymakers, the results indicate a need for strategic investments in technology infrastructure, teacher training, and curriculum integration to maximize the benefits of serious games in STEM education. However, significant limitations were identified, including technological barriers, variability in study quality, and the need for sustained educator support, which may impact generalizability and implementation.ConclusionThis review highlights the transformative potential of serious games as tools for STEM education but emphasizes the importance of addressing key challenges to realize their full benefits. For educators, implementing serious games requires alignment with curriculum goals and access to adequate training and resources. Policymakers are encouraged to support these efforts by providing financial resources and promoting frameworks for ethical, data-secure use of serious games in education. Future research should focus on establishing a globally recognized framework for serious games in STEM, conducting longitudinal studies to evaluate long-term impacts, and exploring diverse educational contexts to ensure inclusive and effective integration.